Ruthenium-catalyzed C–H amination of aroylsilanes. Issue 28 (2nd July 2021) - Yu, Feifei; Shen, Wenzhou; Sun, Yaling; Liao, Yilei; Jin, Shuqi; Lu, Xiunan; He, Rui; Zhong, Liangjun; Zhong, Guofu; Zhang, Jian
Abstract : Acylsilane represents one valuable synthon in synthetic chemistry. We report on ruthenium(ii )-catalyzed ortho -C–H amination of aroylsilanes to provide facile access to synthetically useful imidobenzoylsilanes and tosyl-amidobenzoylsilanes. Abstract : Acylsilane represents a valuable synthon in synthetic chemistry. We report on ruthenium(ii )-catalyzed ortho -C–H amination of aroylsilanes to provide facile access to synthetically useful imidobenzoylsilanes and tosyl-amidobenzoylsilanes. The protocols, with broad substrate scope and excellent functional group tolerance, are enabled with the weak chelation-assistance of acylsilane via C–H cyclometallation.